Patient-controlled hospital admission in psychiatry: A systematic review. (November 2015) - Strand, Mattias; von Hausswolff-Juhlin, Yvonne
Abstract: Background: Patient-controlled admission is a concept that invites patients with long-term mental illness to decide for themselves when inpatient treatment is necessary without a clinician serving as gatekeeper. Aim: To review the current knowledge of patient-controlled hospital admission in adult psychiatry. Method: A systematic literature search was conducted in PubMed/MEDLINE, EMBASE and the Cochrane Library with the aim of identifying all relevant scientific papers from 1990 onwards. Results: Six articles reporting on four different study sites were identified. Detailed account of the models is given and quantitative and qualitative outcome data is reviewed. Rationales behind the concept include increased patient autonomy, promotion of coping skills, early help-seeking, avoidance of power struggles, establishment of an asylum function, reduced time spent in inpatient care and prevention of coercive measures. Quantitative data points toward a dramatic reduction of total time spent in inpatient care and of involuntary admissions in patients with previously high inpatient care consumption, whereas qualitative data indicates that the concept increases patient autonomy, responsibility and confidence in daily life. Conclusion: Patient-controlled admission is a promising novel approach to inpatient care in psychiatry. However, available studies are small and quality of evidence is generally low.